2010
DOI: 10.1007/s00421-010-1353-6
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle telomere length in healthy, experienced, endurance runners

Abstract: Measuring the DNA telomere length of skeletal muscle in experienced endurance runners may contribute to our understanding of the effects of chronic exposure to endurance exercise on skeletal muscle. This study compared the minimum terminal restriction fragment (TRF) length in the vastus lateralis muscle of 18 experienced endurance runners (mean age: 42 +/- 7 years) to those of 19 sedentary individuals (mean age: 39 +/- 10 years). The runners had covered almost 50,000 km in training and racing over 15 years. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 23 publications
4
77
0
3
Order By: Relevance
“…Rae et al reported an inverse relationship between minimum telomere length and long term exposure to endurance exercise (Rae et al, 2010). Kadi et al observed an inverse correlation between minimum SMTL and performance in power lifting .…”
Section: Discussionmentioning
confidence: 99%
“…Rae et al reported an inverse relationship between minimum telomere length and long term exposure to endurance exercise (Rae et al, 2010). Kadi et al observed an inverse correlation between minimum SMTL and performance in power lifting .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many high-performance athletes that are subject to intense training regimens are known to suffer from premature ageing (Wright 2012) including health problems associated with accelerated senescence (Kurz et al 2004). For example, Rae et al (2010) measured the DNA telomere length of skeletal muscle in experienced endurance runners and found that there is an inverse relationship between exposure to endurance exercise and minimum telomere length, and by implication, the proliferative potential of skeletal muscle satellite cells (stem cells). They concluded that endurance running influenced the proliferative potential of stem cells negatively.…”
Section: Discussionmentioning
confidence: 99%
“…To determine effects of endurance training in humans, (Rae et al, 2010) obtained detailed training records and minimum TRF length of the vastus lateralis muscle in 17 well recovered 42.4±6.9 year old endurance runners. 455…”
Section: ) In Contrast To Skeletal Muscle Cells Tl Mean Values In mentioning
confidence: 99%
“…satellite cells). TL in satellite cells is of special interest, since exercise acts to particularly damage muscle tissue (Rae et al, 2010), thus requiring enhanced muscle stem cell proliferation. The cell proliferation and therefore the DNA replication is accompanied by telomere shortening due to the end replication problem, on the one hand, and by telomere lengthening via telomerase, on the other.…”
Section: Introduction and Scopementioning
confidence: 99%
See 1 more Smart Citation